Reviving Australia essays on the history and experience of revival and revivalism in Australian Christianity - Hutchinson, Mark Peter, 1958-; Piggin, Stuart (Sydney, NSW The Centre for the Study of Australian Christianity, Robert Menzies College, Macquarie University, 1994)
Includes bibliographical references.
Keywords: Christianity -- Australia; Christianity -- revivalism; Australia -- civilisation